Growth and characterization of strontium vanadate films deposited by reactive magnetron sputtering - Axel Rouviller; Moussa Mezhoud; Christian Dufour; Clara Grygiel; Ulrike Lüders; Xavier Portier; Fabrice Gourbilleau (APL Materials)
Indium-tin oxide (ITO) is the most commonly used transparent conducting oxide (TCO) but suffers from resource depletion. Among all the alternatives to replace it, SrVO3 is a promising candidate that has been highly studied in recent years. In this study, structural, electrical, and optical properties of 30 nm thick films grown on low-cost substrates by reactive sputtering of a SrVO3 target are presented. The structural, electrical, and optical properties of the obtained films have been compared to those of our previous study in which thin films were grown using a Sr2V2O7 target, illustrating that the use of an SrVO3 target allows us to obtain layers with lower roughness and better opto-electronic properties. Moreover, it was observed that the layers are non-stoichiometric compared to SrVO3, which can explain their semiconducting properties instead of the expected metallic behavior.